2019
DOI: 10.1002/jnr.24385
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D serves as a key executioner of pyroptosis in experimental cerebral ischemia and reperfusion model both in vivo and in vitro

Abstract: Even though ischemic stroke is among the leading causes of death worldwide, the pathogenic mechanisms underlying ischemia reperfusion (I/R) brain injury remain unclear. Gasdermin D (GSDMD), as an important factor of pyroptotic death execution downstream of caspase‐11 (noncanonical inflammasome) and caspase‐1 (canonical inflammasome), may be implicated in I/R injury. The current study aimed to investigate the role and possible underlying mechanisms of GSDMD in pyroptosis during I/R injury. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 36 publications
6
100
2
Order By: Relevance
“…A number of studies have identified that the activation of the Gasdermin family proteins is the biological marker for pyroptosis [26][27][28][29]. Few studies have observed that GSDMD was activated in primary cultured cortical neurons or microglia or BV2 cells undergoing OGD or OGD/R [21][22][23], but the time point of GSDMD activation in these studies is different from that in our study, which may be due to the difference in cell type or culture condition. Our study observed the activation of GSDMD in BV2 and HT22 cells after OGD/R.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…A number of studies have identified that the activation of the Gasdermin family proteins is the biological marker for pyroptosis [26][27][28][29]. Few studies have observed that GSDMD was activated in primary cultured cortical neurons or microglia or BV2 cells undergoing OGD or OGD/R [21][22][23], but the time point of GSDMD activation in these studies is different from that in our study, which may be due to the difference in cell type or culture condition. Our study observed the activation of GSDMD in BV2 and HT22 cells after OGD/R.…”
Section: Discussioncontrasting
confidence: 73%
“…Although some studies have suggested that activation of GSDMD and pyroptosis in microglia and neurons in simulated ischemic conditions in vitro [21][22][23], however, it is still unclear whether there is interplay between microglial and neuronal pyroptosis after I/R, which results in inflammatory propagation. Moreover, there isn't any report about activation of GSDME following cerebral I/R.…”
mentioning
confidence: 99%
“…GSDMD contains~480 amino acids in two domains, and the N-terminal gasdermin domain (GSDMD-N) and the C-terminal gasdermin domain (GSDMD-C) are linked by a long loop. Mounting evidence has demonstrated that GSDMD plays a key role in CNS injury 22,23 . In our study, we also observed that GSDMD was upregulated after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of caspase-1 protects against neuronal death induced by brain ischemic injury, trophic factor withdrawal or Aβ treatment. 14,15 Moreover, inhibiting pyroptosis could alleviate diabetic cardiomyopathy, diabetic nephropathy, and diabetic retinopathy. 16 However, whether pyroptosis is involved in diabetes-induced brain injury has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%